The nomenclatural history of Cienfuegosia tuberculata (Malvaceae) - Fryxell, Paul A.; Harriman, Neil A. (Phytotaxa, 2013)
The names Cienfuegosia digitata and Cienfuegosia tuberculata were published simultaneously by Cavanilles as alternate names for the same species. In another publication (Anonymous 1787) Cienfuegosia tuberculata was used for this species, but the alternative name, C. digitata, was not mentioned. The name C. tuberculata has not otherwise appeared or been accounted for in any subsequent literature until now. It is here formally stated to be a synonym of Cienfuegosia digitata.